2017
DOI: 10.3390/su9101713
|View full text |Cite
|
Sign up to set email alerts
|

Marcellus Shale Fracking and Susquehanna River Stakeholder Attitudes: A Five-Year Update

Abstract: Abstract:The attitudes of Susquehanna River stakeholders regarding natural gas hydraulic fracturing (fracking) in the Marcellus Shale region reflect differing concerns on economic, social, and environmental issues based on gender, education level, and income. The focus on the U.S. State of Pennsylvania section of the Susquehanna River derives from the U.S. States of New York and Maryland, neighbors of Pennsylvania to the immediate north and south, respectively, enacting bans on fracking, while Pennsylvania has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The ndings were drawn from the authors' professional experience and existing literature. [65][66][67][68] 3.3 Identication of potential solutions to hydraulic fracturing Potential solutions are categorized as unique hydraulic fracturing technologies, educational practices, government grants or subsidies, and governmental policies that may improve the current state of hydraulic fracturing. S2 (ESI †) broadly discussed all the identied potential solutions to hydraulic fracturing, which could be integrated with the case-specic solutions to provide robust measures for effective management of all potential hydraulic fracturing activities or shale gas exploitation-related activities in the Fylde community.…”
Section: Understanding Needs Of Stakeholdersmentioning
confidence: 99%
“…The ndings were drawn from the authors' professional experience and existing literature. [65][66][67][68] 3.3 Identication of potential solutions to hydraulic fracturing Potential solutions are categorized as unique hydraulic fracturing technologies, educational practices, government grants or subsidies, and governmental policies that may improve the current state of hydraulic fracturing. S2 (ESI †) broadly discussed all the identied potential solutions to hydraulic fracturing, which could be integrated with the case-specic solutions to provide robust measures for effective management of all potential hydraulic fracturing activities or shale gas exploitation-related activities in the Fylde community.…”
Section: Understanding Needs Of Stakeholdersmentioning
confidence: 99%
“…While studies have shown that there are risks and environmental injustices associated with fracking, there are also benefits. With the rich source of natural gas comes internalized profits and economic growth (Heuer & Yan, 2017). The questions that must be addressed include:…”
Section: Controversymentioning
confidence: 99%
“…When it comes to community advocacy, residents of the Susquehanna River Basin area in Pennsylvania who are affected by fracking have varying opinions and levels of support for the activity (Heuer & Yan, 2017). In a survey of residents of the Susquehanna River Basin, males with lower income tended to support fracking in their vicinity while females who were more highly educated favored a prohibition because of health and safety concerns (Heuer & Yan, 2017). Researchers speculate that the support noted by men with lower income is likely related to the otherwise lack of economic and financial opportunities without fracking (Heuer & Yan, 2017).…”
Section: Advocacy To Address Environmental Injusticementioning
confidence: 99%
“…Although the economic boom that generally accompanies UNGD may have positive effects on the local communities, pollutants and stressors associated with drilling may affect public health in predictable as well as unpredictable ways. While community members and politicians alike voice extensive concern over the impact of UNGD on health [1][2][3] and the importance of research in this area has been emphasized in public health literature, [4][5][6][7][8] few epidemiological studies have quantified its impact on a range of health outcomes to date.…”
Section: Introductionmentioning
confidence: 99%